Strengthening Elementary School Students’ Civic Disposition through Gamified NoHaKi E-Module in Pancasila Education - Hamidaturrohmah, Hamidaturrohmah; Faidah, Nur (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
Rapid digitalization and social transformation have contributed to a decline in students’ civic disposition, posing challenges for Pancasila education in fostering responsible and engaged citizens. This study examines the effect of gamified NoHaKi E-Module on elementary students’ civic disposition in Pancasila Education. A quantitative pre-experimental method with a one-group pretest–posttest design was used. The sample consisted of 40 fifth-grade students at SDN Demaan, Jepara, selected through purposive sampling. Data were collected using a Likert-scale questionnaire covering five aspects: social and moral responsibility, social participation, rule compliance, environmental awareness, and empathy and tolerance. The results showed a significant improvement in civic disposition after the intervention. The mean score increased from 70.0 (pretest) to 81.9 (posttest). The paired-samples t-test indicated a statistically significant difference (t = -6.18, p < 0.001). The highest increases were found in social and moral responsibility (16.88%) and rule compliance (15.62%), indicating stronger awareness of civic values among students. These findings indicate that gamified NoHaKi e-moduls effectively enhance students’ civic disposition by increasing engagement, motivation, and active participation, while supporting the internalization of civic values in elementary education.